Could our patients be better served? A Health literacy assessment of rural community pharmacies - Brandi Jones (Undergraduate Research Journal for the Human Sciences, 2016)
Pharmacy staff and patient health literacy practices were assessed for pharmacies in a rural MO county with many residents at risk for low health literacy. Using AHRQ’s Pharmacy Health Literacy Assessment Tool, overall weaknesses of county pharmacies determined as a result of the Assessment Tour section of the Tool included lack of interpretation services and poor print font size and clarity of leaflets. When a focus group was also conducted as part of the Tool, participants identified several barriers to service including reliance on their doctors, not their pharmacists, for medication information. The pharmacies in this sample were not as effective as they could be in meeting the needs of those with lower health literacy levels, and it is suggested that with some intentional changes, these pharmacies can better serve their patients with low health literacy.
Keywords: Assessment; of; rural; community; pharmacies